The politics of place and the power of the weaker - Arizpe, Lourdes (2002)
Lourdes Arizpe in commenting on the lead paper argues that as women mobilize they bring about a new awareness of our individual and collective places in the world. These experimental grounds, `glocalities', are building new concepts of belonging and of participating where different politics are being expressed and negotiated. - Reproduced.
Keywords: Women